Effectiveness of levamisole in the treatment of patients with severe COVID-19: a randomized controlled clinical trial - Morteza Pourahmad; Rasool Soltani; Mohammad H Noroozi; Farzin Khorvash; Behrooz Ataei; Manijeh Shams; Fatemeh Nikokar (Journal of Infection in Developing Countries)
Introduction: Inflammation plays a role in coronavirus disease 2019 (COVID-19) pathophysiology and anti-inflammatory drugs may help reduce the disease severity. Levamisole is an anthelmintic drug with immunomodulatory and possible antiviral effects. This study aimed to evaluate the role of levamisole in the treatment of patients with COVID-19.